2018
DOI: 10.1111/ahe.12401
|View full text |Cite
|
Sign up to set email alerts
|

The dorsal skin structure contributes to the surface bacteria populations of Sunda Porcupine (Hystrix javanica)

Abstract: Skin becomes the largest organ in the body and protects its own inner layer. The structure and chemical composition of the skin contribute to skin condition and affect the habitat of certain bacteria. The Sunda Porcupine is one of endemic animals of Indonesia which possesses quill as the main derivate of its skin and as a defence tool against predators. The present study used nine adults (five females and four males) of Sunda Porcupine and aimed to observe the correlation of skin structure with bacterial popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 28 publications
3
29
0
Order By: Relevance
“…Skin with high density of sebaceous glands will have higher alpha tocopherol content (Thiele et al, 1999). Our previous studies showed that sebaceous gland density in TD region is higher than in LD region (Prawira et al, 2018b). The difference in level between male TD and female TD may also be influenced by different hormonal activity between the sexes affecting the activity of the sebaceous glands (Cunliffe & Forster, 1987;Fritsch et al, 2001).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Skin with high density of sebaceous glands will have higher alpha tocopherol content (Thiele et al, 1999). Our previous studies showed that sebaceous gland density in TD region is higher than in LD region (Prawira et al, 2018b). The difference in level between male TD and female TD may also be influenced by different hormonal activity between the sexes affecting the activity of the sebaceous glands (Cunliffe & Forster, 1987;Fritsch et al, 2001).…”
Section: Resultsmentioning
confidence: 98%
“…Skin characteristics in the LS region showed lower density of the quill clusters than in the TD region (Prawira et al, 2018b) allow many parts of the skin to be exposed to the environment such as sunlight, soil, dust, etc. more than the TD region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quills of all porcupine species are larger, stiffer and stronger than its hairs and act as means of self-defense from predators or other threats (Mohr 1965;Myers 2001;van Weers 1983). Previously we exhibit that the appearances of dorsal skin surface of the porcupine is wavy due to protrusion of quill follicles in the form of clusters and varying in size according to the location and quill type (Prawira et al 2018b). The quill follicles are known as the dominant structure in the skin of this species (Prawira et al 2018a).…”
Section: Introductionmentioning
confidence: 93%
“…Sizes of the sebaceous glands of quills were relatively larger compared to the hairs' glands. Glandular lobules of quill sebaceous gland were composed of well-developed sebaceous acinar cells with lipid vacuoles varying in size (Prawira et al 2018b).…”
Section: Introductionmentioning
confidence: 99%